Kursus Bimbel Gratis dan Menyenangkan Bahasa dan Matematika di SMP Beerseba Pekanbaru - Ardina Br Saragih; Celine Inviolata Hutagalung; Jayadi Setia Oktafiana; Johannes P Nababan; Kristin Y. S. Manik; Sthepanie Turnip; Winda C. Br. Manurung; Juli Antasari Br. Sinaga (Utan Kayu Publishing, 2022)
The Community Service Program (PkM) activity is one of the compulsory subjects that students of the Faculty of Teacher Training and Education (FKIP) HKBP Nommensen University (UHN) Medan must take in order to develop students' teaching potential as prospective educators or as prospective educators who are professional and ready to enter the world of education. PkM activities supplement and complement the knowledge and skills acquired by students while in college. This program serves a purpose and serves a function, namely to give students with the opportunity to become professional education employees in order to increase students' knowledge and skills as professionals. Personality competence, professional competence, personal competence, and social competence are all required competencies for educators. The PkM program will equip students with real-world experience as aspiring educators. The PkM program encourages students to continue to strive towards the development of attitudes and personalities as educators, especially mature attitudes in behaving and thinking, discipline in carrying out their tasks and commitments, and the ability to adapt to their environment, institution, or society.